Development of an Antibacterial Coaxial Bionanocomposite Based on Electrospun Core/Shell Fibers Loaded with Ethyl Lauroyl Arginate and Cellulose Nanocrystals for Active Food Packaging - Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C; Velasquez, E (Elsevier Ltd, 2022)
Developing antimicrobial electrospun bionanocomposites with core/shell structure is an innovative strategy for producing active food packaging materials. The aim of this study was developing an antibacterial electrospun mat based on polylactic acid (PLA) coaxial fibers containing ethyl lauroyl arginate (LAE) and cellulose nanocrystals (CNC) through electrospinning. The effect of the coaxial structure and the incorporation of both components on the structural, thermal and release properties of the electrospun PLA was analyzed. LAE release studies were carried out in 10% and 95% EtOH, and results correlated with antibacterial assays. Structural analysis only indicated some chemical interactions through hydrogen bonding between PLA and LAE in the core structure. The incorporation of LAE and CNC produced a plasticizing effect in the PLA, and the crystallinity of polymer was maintained by the presence of CNC. Core/shell structure and the presence of CNC slowed down the LAE release. Furthermore, the bionanocomposite exhibited strong bactericidal activities. © 2021 Elsevier Ltd